Gender, Care and Opportunities of Welfare Capitalism in Lithuania - Maslauskaitė, Aušra (Sociologija. Mintis ir veiksmas, 2004)
The research aims to evaluate the opportunities for the welfare capitalism in the Lithuanian society and is directed toward the analysis of cultural conditions, which largely determine the success and efficiency of the social policy actions. The research objective is the analysis of gender inequalities, which are produced and reproduced in the family. Unequal distribution of care in family influences the gender opportunities, discriminatory attitudes and the development of gender modernization. The institutionalisation of care in most EU states is seen as one of the key factors in solving gender and family policy problems. The interplay of prevailing modern gender identities and the institutionalisation of care promote the equality of social rights, enhance women’s participation and help solving the family policy issues. The research examines the positioning of care in Lithuanian gender identities and questions to what extent the care institutionalisation in Lithuania may facilitate the overcome of gender inequalities and stimulate the development of equal opportunities and welfare capitalism. The research is structured upon several main lines. First, it discusses the theoretical issues of welfare capitalism and gender modernization, second, the sociological dimensions of the care concept. The third theme is dedicated to the analysis of the Lithuanian society’s values and attitudes toward gender and care.